Measurement Mental Health of Expectant Mothers and Their Relation to Some Socio-Economic Demographic Variables in Al-Emis Hospital, Gizan City, Saudi Arabia (2017 – 2018) - Kawkab, Al-Masnaah; Magda, Elhadi; Ebtisam, Mahmood (International Journal For Research In Health Sciences And Nursing, 2021)
A descriptive study aimed to measure the mental health of pregnant mothers and their relationship to some demographic, social- economic variables in Al-meis Jizan Hospitals (2017-2018). Researcher used the questionnaire.,. the researcher distributed (360) forms. (300) forms were retrieved, and then the researcher empties the data. And its analysis by SPSS statistical analysis program. The study reached many results, the most important of which was: pregnant mental health was low. And no statistically differences between the mental health and some socio-economic demographic variables, (age, education &income) researcher made many recommendations and proposals, the most important of them: The relevant persons like husbands , other family members and society around her and the relevant bodies, especially the Ministry of Public Health and Population and the World Health Organization, should pay attention to the mental health of pregnant mothers, and there must be continuous awareness by The appropriate authorities for pregnant women in appropriate ways to maintain their mental health, and the pregnant woman must check-up periodically during pregnancy to ensure her safety and the safety of the fetus, 4. The researcher suggests that there be a medical program that works on early detection of mental health diseases so that suspicious cases are transferred to specialized centers in the area where the pregnant woman resides, and the family and society should create the appropriate environment for pregnant mothers and keep them away from anything that affects their physical and mental health, and recommends the researcher conducts more studies and researches, especially that this aspect of science many researchers complain about the lack of research in it that is not commensurate with the size of the problem with society, the researcher suggests preparing an educational program that will be directed to the pregnant mothers in all hospitals and health centers to increase the awareness, Training of mothers and husbands on knowing the mental effects and how to provide support. As the researcher recommends that there be mechanisms to activate international laws to protect pregnant women in war and conflict areas and in the event of natural disasters, and to have priority in protection and care.